The optimal investment size in the electricity sector in EU countries - Mathieu Petit; Karel Janda (Charles University in Prague, Institute of Economic Studies (IES), 2024)
This paper aims to estimate the optimal environmental policy in the elektricity generation sector for each of the EU countries maximizing total welfare. The study uses a recently proposed theoretical corporate finance model and empirically estimate each of its components using the current state of the literature to derive the estimated optimal investment size and greenhouse gas abatement activities. Results indicate that a social planner would not significantly reduce the carbon intensity of the EU electricity generation sector but rather keep its industry size well below current levels.
Keywords: C54; G38; Q41; Q54; 330; investment size; abatement activity; electricity demand; social cost of carbon; carbon intensity; marginal abatement cost curve